Issues and challenges in implementing cervical cancer screenings in the emergence of HPV vaccination in Thailand - Juntasopeepun,P. (Elsevier, 2015)
The discovery of the HPV vaccine has been a major breakthrough in preventing cervical cancer and other HPV-related diseases around the globe. Cervical cancer is a significant public health problem in Thailand. Despite the long-time availability of cervical cancer screening programs in Thailand, the uptake among the target female population remains low. HPV vaccines were approved by the Food and Drug Administration of Thailand in 2007. As of March 2011, due to financial limitations, HPV vaccines have still not been included in the national immunization program under the public health benefit plans although individuals has the option to pay privately for the vaccine. This paper discusses the issues and challenges in implementing cervical cancer screening programs in the era of HPV vaccination in Thailand. Recommendations to increase the uptake of cervical cancer screening and further research to inform a policy regarding the cervical cancer screening measures are proposed. © 2011 Royal College of Nursing, Australia.